Chinese EFL learners different from English natives in cataphora resolution: Evidence from eye-tracking studies - Wang, Tao; Geng, Mingyao; Wang, Yue; Zhao, Min; Zhou, Tongquan; Yang, Yiming (Frontiers in Psychology, 2023)
Previous studies on English natives have shown that encountering an English cataphoric pronoun triggers an active search for its antecedent and this searching process is modulated by syntactic constraints. It remains unknown whether the conclusion is universal to EFL (English as a Foreign Language) learners, particularly those with distinct L1 like Chinese in linguistic typology. Therefore, this study used two eye-tracking experiments to investigate how Chinese EFL learners resolve English cataphora. The experiments adopted the gender-mismatch paradigm. Experiment 1 investigated whether Chinese EFL learners with different proficiency would adopt the similar processing pattern to English natives and found that gender congruency elicited longer reading times than gender incongruency between the first potential antecedent and the cataphoric pronoun, the effect early observed in high-proficiency relative to low-proficiency learners. Experiment 2 explored whether the cataphora resolution process was modulated by Binding Principle B and revealed that longer first fixation durations and first pass reading times were observed in gender-mismatch than in gender-match conditions no matter the antecedents are binding-accessible or not while longer regression path durations occurred in gender-mismatch than in gender-match conditions only as the antecedents are binding-accessible. Taken together, these results indicate that Chinese EFL learners also adopt an active search mechanism to resolve cataphoric pronouns, yet along a processing path distinct from English natives’. Specifically, Chinese EFL learners predictively link a cataphoric pronoun to the first potential antecedent in the sentence but only a gender-matching antecedent can prompt them to engage in deep processing of the antecedent. Moreover, the processing time varies with the learners’ English proficiency. Furthermore, unlike native English speakers’ early application of syntactic constraints in their cataphora resolution, Chinese EFL learners try to establish co-reference relations between cataphoric pronouns and antecedents regardless of following or flouting Binding Principle B in early processing stages whereas they exclusively link the cataphoric pronouns to the binding-accessible antecedents in late processing stages. This study adds evidence to the Shallow Structure Hypothesis whereby L2 learners resort to lexical prior to syntactic cues to process sentences in general, which is just opposite to the fashion adopted by the natives.